Ozone Decreased Enteric Methane Production by 20% in an in vitro Rumen Fermentation System - Zhao, Lucy; Caro, Eleonora; Holman, Devin B.; Gzyl, Katherine E.; Moate, Peter J.; Chaves, Alex V. (Frontiers in Microbiology, 2020)
Ozone (O3) is volatile, highly oxidative, and has theoretical potential to reduce ruminant enteric methanogenesis by interactions between archaea and bacteria, and substrate and oxygen. The effects of O3 on the rumen microbiota, fermentation parameters and CH4 emissions were studied through in vitro fermentation using a RUSITEC apparatus with O3 dissolved in the salivary buffer. The substrate consisted of maize silage or grain concentrates, and the treatments were 1) control (no O3) and 2) O3 at 0.07±0.022 mg/L in the buffer. A four-day adaptation period followed by a six-day experimental period was used for measuring gas production and composition, as well as fermentation characteristics, which included ruminal volatile fatty acids (VFA) and liquid- and solid-associated microbial communities. Ozone treatment decreased total gas production by 15.4%, most notably CH4 production by 20.4%, and CH4 gas concentration by 5.8%, without compromising dry matter digestibility of either maize silage or grain concentrates. There were no significant effects of O3 treatment on VFA production or pH. Ozone treatment reduced the relative abundance of methanogens, particularly Methanomicrobium. This study demonstrates the potential use of O3 as a method to reduce ruminant enteric methanogenesis.